Virtual Reality and Augmented Reality for Heart Failure Patients: Literature Review: Virtual Reality dan Augmented Reality Bagi Pasien Gagal Jantung: Literature Review - Kusumastuti, Kartikaningtyas; Herawati, Tuti (Politeknik Kesehatan Kemenkes RI Jakarta I, 2024)
Virtual reality (VR) and augmented reality (AR) in the health sector are increasingly being used. However, there is limited study on the use of VR and AR in nursing care for heart failure. Long-term care for heart failure patients is a challenge as well as an opportunity for nurses to apply VR and AR, so that therapy modalities become more varied, interesting, and increase patient compliance. The aim of this literature study is to explore the use of VR and AR for heart failure patients. Articles were obtained from the ScienceDirect, PubMed, Clinical Key, SAGE, ProQuest and SpringerLink databases published in 2019-2023, using the keywords